Effective electrochemical degradation of Piroxicam by RUO2/TAO2/IRO2-TIO2 mesh anodes - GANESAN SIVARASAN,; LINGASSAMY ARUL PRAGASAN, (International Journal of Pharma and Bio Sciences, 2018)
The widely used non-steroidal anti-inflammatory drugs (NSAIDs) are detected on the order of ng/L to g /L in the effluent of sewage treatment plants and river water. These pharmaceutical drugs are resistant to degradation. Therefore the powerful treatment process is needed for the degradation of pharmaceutical contaminants. The main objective of this study was to investigate the Electrochemical (EC) degradation of NSAIDs of Piroxicam (PCM) by using RuO2/ IrO2/ TaO2 coated Ti- mesh anodes. Cyclic voltammetric study of oxidation and reduction when we added to the 0.1M Na2SO4 supporting electrolyte, the oxygen evolution reactions and hydrogen evolution reactions are observed at 0.8 and 0.5 V vs. Ag/AgCl (scan rate at 20 mV/s). These optimized results reveal that the EC oxidation on RuO2/TaO2/IrO2-TiO2 electrode was totally irreversible. The degradation efficiency of PCM was further confirmed by UV-Spectra analysis. The effects of the oxidative potential, current density, initial concentration of PCM, electrolysis time, electrolyte concentration and initial pH evaluated. At the optimum conditions (current density = 5 mA/cm2, initial concentration = 20 mg/L, pH = 5.4, and electrolyte concentration = 0.1M Na2SO4), after 180 min, the removals of PCM concentration, chemical oxygen demand (COD) and total organic carbon (TOC) were about 99.9%, 71.6%, and 56.7%, respectively. The parameters, K value, half-life (t1/2) and R2. The rate constant (k) values were calculated using linear regression. The PCM degradation reaction followed pseudo-first-order kinetics (R2>0.90). The results showed that the electrochemical oxidation, using RuO2/ IrO2/ TaO2 coated TiO2- mesh anode as highly effective material for degradation of NSAIDs.